Cerebro-placental ratio as a prognostic factor of fetal outcome in women with hypertensive disorders complicating pregnancy during third trimester - K., Sahana; B., Suma K.; R., Nischay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: CPR is emerging as an important predictor of adverse pregnancy outcome and helps in management of high risk pregnancy. Therefore we undertook the study to find the correlation of CPR with perinatal outcomes in women with hypertensive disorder complicating during third trimester. Methods: 128 patients with hypertensive disorder of pregnancy, ≥32 weeks of singleton gestation, were randomly selected during their hospital visit. They were subjected to USG Doppler study to calculate MCA/UA pulsatility index-CPR. The CPR<1 was considered abnormal and >1 as normal. These results were compared with the perinatal outcome and adverse fetal outcome. Results: The present study revealed that the incidence of adverse outcomes like Apgar score <7 (36.5%), still birth (15.9%), NICU admission (69.8%) and LBW i.e. <2500 gm (68.3%) were significantly higher in abnormal CPR than normal CPR. Conclusions: Abnormal CPR is valuable in predicting the outcome of hypertensive disorders in pregnancy. CPR is an easy procedure which can be included in the routine antenatal sonographic evaluation to predict poor perinatal outcome and to detect or recognize those fetuses at risk.